Drop-Jump Landing Varies With Baseline Neurocognition - Daniel C. Herman; Jeffrey T. Barth (2016)
Neurocognitive status may be a risk factor for anterior cruciate ligament (ACL) injury. Neurocognitive domains such as visual attention, processing speed/reaction time, and dual-tasking may influence ACL injury risk via alterations to neuromuscular performance during athletic tasks. However, the relationship between neurocognition and performance during athletic tasks is not yet established.Athletes with low baseline neurocognitive scores will demonstrate poorer jump landing performance compared with athletes with high baseline neurocognitive score.Controlled laboratory study.Neurocognitive performance was measured using the Concussion Resolution Index (CRI). Three-dimensional kinematic and kinetic data of the dominant limb were collected for 37 recreational athletes while performing an unanticipated jump-landing task. Healthy, nonconcussed subjects were screened using a computer-based neurocognitive test into a high performers (HP; n = 20; average CRI percentile, 78th) and a low performers (LP; n = 17; average CRI percentile, 41st) group. The task consisted of a forward jump onto a force plate with an immediate rebound to a second target that was assigned 250 milliseconds before landing on the force plate. Kinematic and kinetic data were obtained during the first jump landing.The LP group demonstrated significantly altered neuromuscular performance during the landing phase while completing the jump-landing task, including significantly increased peak vertical ground-reaction force (mean ± SD of LP vs HP: 1.81 ± 0.53 vs 1.38 ± 0.37 body weight [BW]; P < .01), peak anterior tibial shear force (0.91 ± 0.17 vs 0.72 ± 0.22 BW; P < .01), knee abduction moment (0.47 ± 0.56 vs 0.03 ± 0.64 BW × body height; P = .03), and knee abduction angle (6.1° ± 4.7° vs 1.3° ± 5.6°; P = .03), as well as decreased trunk flexion angle (9.6° ± 9.6° vs 16.4° ± 11.2°; P < .01).Healthy athletes with lower baseline neurocognitive performance generate knee kinematic and kinetic patterns that are linked to ACL injury.Neurocognitive testing using the CRI may be useful for identification of athletes at elevated risk for future ACL injury.